IMPLEMENTASI SISTEM MONITORING MENGGUNAKAN ZABBIX DAN NOTIFIKASI REALTIME TELEGRAM UNTUK JARINGAN INTERNET BSI (BALI SMART ISLAND) DI KABUPATEN JEMBRANA - Sugiarta, I Kadek; I Gede Juliana Eka Putra; I Nyoman Yudi Anggara Wijaya (ITB Ahmad Dahlan Jakarta, 2025)
With the advancement of information and communication technology, society has become increasingly dependent on access to information through the internet. However, this growing reliance has also led to a rise in the frequency of network disruptions, which can cause delays in information dissemination and interfere with institutional operations. PLN ICON PLUS, as an Internet Service Provider (ISP), faces the challenge of monitoring 123 routers used by the customers of the Jembrana Regency Communication and Information Office (Diskominfo). This research highlights the importance of implementing a network monitoring system using Zabbix, which can provide real-time notifications through Telegram to detect disruptions and minimize downtime.Currently, PLN ICON PLUS does not yet have an effective monitoring system, resulting in delays in addressing network issues. By adopting a more advanced monitoring solution, network performance is expected to improve, enabling technical teams to respond quickly and efficiently to disruptions, thereby enhancing service quality for Diskominfo Jembrana customers. The final results of the monitoring system show that it can operate properly and consistently send real-time notifications to Telegram whenever disruptions occur on devices or network services. This proves that the system can improve the responsiveness of the technical team in handling issues and minimizing downtime. Thus, the monitoring system is considered effective in supporting proactive and efficient network management.